2008
DOI: 10.1016/j.jalz.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 domain interaction: Synaptic and cognitive deficits in mice

Abstract: BackgroundApolipoprotein E4 (apoE4), the major genetic risk factor for Alzheimer's disease (AD) and other neurodegenerative diseases, has three structural and biophysical properties that distinguish it from the other isoforms—domain interaction, reduced stability, and lack of cysteine. Assessing their relative contributions to effects of apoE4‐associated pathogenesis in AD is important from a mechanistic and therapeutic perspective, that is not possible using human apoE transgene or knock‐in models.MethodsWe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 50 publications
5
47
0
1
Order By: Relevance
“…2, c and d, and 3, a-c). Furthermore, previous data seem to favor the loss of the excess proliferating cells via apoptosis since; even though some DCXpositive cells may retain their multipotentiality (74) and thus are likely to differentiate into glia, Zhong et al (18) reported that there was neither gliosis nor difference in NeuN-positive cell counts in the hippocampus of Arg-61 versus C57BL/6J mice. Meanwhile, the fact that we observed even a higher level of cleaved caspases-3 in older animals seems contrary to our earlier speculation about potential apoptosis of most of the mitotic DCX cells in young Arg-61 mice.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…2, c and d, and 3, a-c). Furthermore, previous data seem to favor the loss of the excess proliferating cells via apoptosis since; even though some DCXpositive cells may retain their multipotentiality (74) and thus are likely to differentiate into glia, Zhong et al (18) reported that there was neither gliosis nor difference in NeuN-positive cell counts in the hippocampus of Arg-61 versus C57BL/6J mice. Meanwhile, the fact that we observed even a higher level of cleaved caspases-3 in older animals seems contrary to our earlier speculation about potential apoptosis of most of the mitotic DCX cells in young Arg-61 mice.…”
Section: Discussionmentioning
confidence: 98%
“…This cognitive deficit has been attributed, among other factors, to certain pathologies associated with early stage AD in human subjects, namely synaptic degeneration (43). This may be as a result of astrocyte dysfunctions in the Arg-61 mouse (18). However, it is worth pointing out that no deficit was found in 12-month-old Arg-61 mice during the training phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies suggest that APP plays a protective role post-TBI (Thornton, Vink, Blumbergs, & VanDen Heuvel, 2006), individuals with APOE ε4 + genotype experience increased post-injury Aβ deposition and reduced Aβ clearance (Hartman et al, 2002), which may in turn lead to an increased risk of Aβ plaque formation characteristic of dementia pathology. Compared to APOE ε3, the APOE ε4 isoform of the apolipoprotein E is also less able to repair synapses and protect neurons in the event of injury (Zhong, Scearce-Levie, Ramaswamy, & Weisgraber, 2008) (Katzman et al, 1996;Rohling et al, 2011;Sundstrom et al, 2007;Tang et al, 1996). The majority of these studies have included participants carrying the ε2 allele within the reference group despite evidence that ε2 may protect against degenerative neuropathology (Liu et al, 2013).…”
mentioning
confidence: 99%